Microwave assisted combustion synthesis of pure- and Ni-doped yttrium iron garnet ferrites - Siti Nor Ain, Abdul Mubin; Rodziah, Nazlan; Idza Riati, Ibrahim; Ros Azlinawati, Ramli; Mohamad Ashry, Jusoh (AIP Publishing, 2025)
In this research, the magnetic characteristics of pure and Ni-doped yttrium iron garnet (YIG) fabricated using a conventional solid-state technique followed by a microwave-assisted combustion process have been investigated. The study specifically focused on the changes in structural and microstructural properties of the samples and their influence on the magnetic properties with variations of microwave power and microwave sintering durations on both samples. The X-ray diffraction analysis of both samples confirmed the formation of a cubic garnet structure, regardless of composition and microwave level. The broadening of XRD peaks after milling reflects a natural consequence of milling which dictates a reduced crystallinity and disordering of the atomic arrangement in the structure, as well as defective interface creation due to the milling impact. By microwave sintering, increased microwave power and optimized sintering durations enhance the crystallinity of the overall samples. This contributes to the enhancement of magnetic parameters, i.e. increasing saturation magnetization and reducing coercivity. Moreover, microwave sintering provides uniform heating that minimizes thermal gradients, reducing the risk of localized overheating or underheating of the material. As a result, a more uniform grain size distribution is achieved under controlled microwave parameters. The incorporation of nickel was found to significantly enhance the saturation magnetization in Ni-doped YIG from 0.178 to 0.392 emu/g compared to pure YIG which increases from 0.01 to 0.29 emu/g with prolonged sintering durations from 10 to 30 minutes at fixed microwave power of 800 W. The enhanced magnetization can be attributed to the increased net magnetic moment in Ni-doped YIG and the enlargement of particle sizes, which facilitates improved alignment of magnetic moments with external magnetic fields.